2007
DOI: 10.1007/s10151-007-0357-7
|View full text |Cite
|
Sign up to set email alerts
|

Short-term results of Karydakis flap for pilonidal sinus disease

Abstract: These data provide evidence that the Karydakis flap technique might be performed even in potentially infected tissue. Although a considerable number of wound-related complications was observed in the Karydakis flap group, the majority of patients had primary healing. Thus, from our viewpoint, the Karydakis flap seems to be a potential alternative to simple excision in infected pilonidal sinus disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
2
7

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 22 publications
2
39
2
7
Order By: Relevance
“…A selection bias in that study is probable, because the decision to close the wound or leave it open was influenced by the surgeon's assessment of the degree of contamination. 28 In contrast to Petersen et al, 28 the results in this study show a significant difference, with worse outcome in patients with acute infections undergoing definitive surgery. This finding is important, because patients with wound complications after primary closure tend to have a higher incidence of recurrence.…”
Section: Discussioncontrasting
confidence: 56%
“…A selection bias in that study is probable, because the decision to close the wound or leave it open was influenced by the surgeon's assessment of the degree of contamination. 28 In contrast to Petersen et al, 28 the results in this study show a significant difference, with worse outcome in patients with acute infections undergoing definitive surgery. This finding is important, because patients with wound complications after primary closure tend to have a higher incidence of recurrence.…”
Section: Discussioncontrasting
confidence: 56%
“…Al-Kha yat et al 10 similarly reported sur gi cal si te in fec ti on ra te as 12% by using cep ha zo lin plus met ra ni da zo le com bi na ti on for 24-48 ho urs in a se ri es of Kary da kis pro ce du re. Pe ter sen et al 18 ac hi e ved exactly the sa me wo und in fec ti on ra te after per for ming the flap tech ni qu e, but used a sing le do se pre o pe ra ti ve am pi cil lin-sul bac tam Anyan wu and col le a gu es 12 re por ted a so mew hat lo wer in fec ti on rate (10.7%) with a sing le do se bro ad-spectrum an ti bi o tic. 18 One of the lo west in fec ti on ra tes af ter Kary da kis pro ce du re was re por ted by Bes sa, 8 who used a third ge ne ra ti on cep ha los po rin and met ra ni da zo le for 48 ho urs.…”
Section: Discussionmentioning
confidence: 99%
“…Pe ter sen et al 18 ac hi e ved exactly the sa me wo und in fec ti on ra te after per for ming the flap tech ni qu e, but used a sing le do se pre o pe ra ti ve am pi cil lin-sul bac tam Anyan wu and col le a gu es 12 re por ted a so mew hat lo wer in fec ti on rate (10.7%) with a sing le do se bro ad-spectrum an ti bi o tic. 18 One of the lo west in fec ti on ra tes af ter Kary da kis pro ce du re was re por ted by Bes sa, 8 who used a third ge ne ra ti on cep ha los po rin and met ra ni da zo le for 48 ho urs. Ho we ver, a stri kingly high in fec ti on ra te (26%) af ter Kary da kis pro ce du re was re por ted re cently in a se ri es in which no an ti bi o tic proph yla xis was used in Tur key.…”
Section: Discussionmentioning
confidence: 99%
“…Al considerar la serie global de 100 pacientes en este período, la relación es exactamente 1:1, lo que contrasta con las series anglosajonas que muestran sistemáticamente un predominio del sexo masculino de 3:1, proporción que se eleva a 17:1 en los países mediterrá-neos [3][4][5][6][16][17][18] . Diferencias raciales en aspectos constitucionales como la profundidad del surco ínter glúteo, la obesidad y el hirsutismo se han invocado como posibles causas de esta distribución por género tan sorprendente en nuestro medio, pero la evidencia no apoya esta teoría 12,19 .…”
Section: Discussionunclassified
“…En esta serie programada en forma ambulatoria no hemos tenido casos de recidiva con un seguimiento promedio de 30 meses, cifra que en nuestra serie global alcanza al 1,19% (1/84), luego de un período de observación promedio de 49 meses (extremos 6-88), lo que confirma lo publicado por otros autores con la técnica 4,5,[7][8][9][10][11][16][17][18]21,22 . En conclusión, la resección asimétrica de Karydakis ambulatoria no afecta los buenos resultados que exhibe la técnica en términos de complicaciones, tiempo de cicatrización y recidiva, por lo que se recomienda como técnica de elección en la gran mayoría de los casos de EPSC.…”
Section: Discussionunclassified